Mammographic features of tuberculous axillary lymphadenitis - Muttarak M. (2014)
The clinical and mammographic findings of 10 patients with pathologically proven tuberculous axillary lymphadenitis were reviewed. The cases were identified from 10 173 mammograms performed over 6 years at Maharaj Nakorn Chiang Mai University Hospital. The 10 patients were aged 31-65 years. All cases were initially diagnosed to have breast carcinoma with axillary nodal metastases. Eight patients presented with axillary swelling, while two presented with breast enlargement. None of these cases had a palpable breast mass. Associated supraclavicular, cervical or groin nodes were found in seven cases, and two patients had evidence of pulmonary tuberculosis. All lesions were unilateral, affecting the right side in eight cases and left side in two cases. On mammogram, the axillary nodes were enlarged and homogeneously dense. The nodes were sized 2.5-5 cm. Nodal margins were variable. Some nodes were matted. Macrocalcifications were noted in three cases. Ipsilateral breast oedema without mass or microcalcifications was present in two cases. Patients with tuberculous axillary lymphadenitis have large homogeneously dense nodes with either well- or ill-defined margins. It is impossible to differentiate tuberculous from malignant nodes. The presence of macrocalcifications might suggest tuberculous axillary lynphadenitis. Biopsy of enlarged axillary nodes is necessary to determine its aetiology.